The European Common Space: Extending the Use of Anchoring Vignettes. (22nd July 2014) - Bakker, Ryan; Jolly, Seth; Polk, Jonathan; Poole, Keith
<x content-type="archive" xml:space="preserve">Abstract</x> In this article, we combine advances in both survey research and scaling techniques to estimate a common dimension for political parties across the member states of the European Union. Most previous scholarship has either ignored or assumed cross-national comparability of party placements across a variety of dimensions. The 2010 wave of the Chapel Hill Expert Survey includes anchoring vignettes which we use as "bridge votes" to place parties from different countries on a common space. We estimate our dimensions using the "blackbox" technique. Our results demonstrate both the usefulness of anchoring vignettes and the broad applicability of the blackbox scaling routine. Further, the resulting scale offers a cross-nationally comparable interval-level measure of a party's left/right ideological position with a high degree of face validity. In short, we argue that the left/right economic dimension travels well across European countries.